Geological characteristics and gas-bearing evaluation of coal-measure gas reservoirs in the Huanghebei coalfield - Shao, Yubao; Wang, Huaihong; Guo, Yinghai; Huang, Xinglong; Wang, Yongjun; Zhao, Shushan; Zhu, Yuzhen; Shen, Lijun; Huang, Xin; Song, Yu; Wang, Ming; Cui, Kai; et al. (Frontiers in Earth Science, 2023)
By studying the source reservoir geochemical characteristics, reservoir cap physical properties, gas-bearing characteristics and reservoir forming types of the coal-measure gas (CMG) accumulation system, the potential of CMG resources in the Huanghebei Coalfield was determined, and the sedimentary reservoir control mechanism was analyzed, which is of great significance for the orderly development of CMG reservoirs. CMG in the Huanghebei Coalfield mainly includes shale gas (SG), coalbed methane (CBM) and a small amount of tight sandstone gas, limestone gas and magmatic rock gas, with abundant resources, including CBM resources (137.89×108 m3) and SG resources (2100.45×108 m3). CMG rocks mainly include shale and coal seams of the marine terrestrial transitional facies Taiyuan Formation and continental facies Shanxi Formation, providing a favorable material basis for CMG enrichment. The coal seams are largely mature to highly mature, with a satisfactory hydrocarbon generation potential and reservoir connectivity. They are low-porosity, low-permeability, underpressurized and undersaturated reservoirs. The shale organic matter is primarily Type II, with a moderate organic matter abundance. The material is at the middle- to high-maturity stage, provides a suitable hydrocarbon generation potential, belongs to low-porosity and low-permeability reservoirs, and exhibits favorable fracturing properties. There are several stable and independent gas-bearing systems among the coal measures. The CMG accumulation combination types are mostly self-sourced gas reservoirs and self-sourced+other-source near-source gas reservoirs, followed by other-source gas reservoirs. CBM and SG fulfill vertical and horizontal regulatory roles, respectively.